Epidemiology of nosocomial infections in an intensive care unit at a tertiary care hospital in India: A retrospective study - Khan, Mohd Saif; Kundra, Pankaj; Cherian, Anusha; Joseph, Noyal M; Sistla, Sujatha (International Journal of Infection Control, 2015)
Critically ill patients are at increased risk of developing nosocomial infection. Hospitals in developing countries are facing higher incidence of this problem. The aim of this study was to assess the epidemiology of infections in hospital. A retrospective study was conducted at CCU of a tertiary care teaching hospital in South India. All patients who stayed in ICU for more than 48 hours were included in the study. Relevant data on demographics, ICU length of stay, co-morbidities, pre-admission infections and number of devices were recorded from case records. The culture and sensitivity reports were accessed from the microbiology lab registers. Chi square, unpaired t-test and Fisher’s exact test were used wherever applicable. Out of 315 patients included in the study, 93 patients (29.5%) developed 126 episodes of ICU acquired infections (Incidence density rate; 70.3/1000 ICU days), of which common nosocomial infections were pneumonias (15.5%), urinary tract infections (8.9%), blood stream infections (8.2%) and surgical site infections (7%). Patients who acquired infections in ICU had longer ICU stay and received mechanical ventilation for longer hours. The most common isolates were Pseudomonas aeruginosa (24.9%), Acinetobacter baumannii (23.1%). In logistic regression analysis, following risk factors were significantly associated with higher infection rates: medical category, emergency surgery, diabetes, presence of tracheostomy and total parenteral nutrition (TPN). In conclusion TPN, medical category, emergency surgery, diabetes mellitus and presence of tracheostomy were significant risk factors which lead to higher infection rate. These data will help reinforce the infection control measures.